Sexualized Performance Athletes: An exploratory ZMET study of female athletes’ perceptions - Evert, Malin (2020)
The focus of this study is on media images of sportswomen that have both appearance and athletic elements (termed sexualized performance athlete) and it theorizes and empirically investigates consumer attitudes and perceptions in relation to sexualized performance imagery. Since the purpose of this study was to gather deep consumer insights, the Zaltman Metaphor Elicitation Technique (ZMET) was used to investigate attitudes, thoughts and feelings of young, female and athletic participants (n=10) in relation to sexualized performance imagery. Using ZMET, three main themes emerged: (1) Sexualized and athletic elements of sexualized performance athlete imagery (2) Symbolic Metaphors for sexualized performance athletes (3) Attitudes, beliefs and perceptions of sexualized performance imagery of athletes and its connection to society and reality. The method allowed to uncover conscious and unconscious consumer thought and gain a deep understanding of attitude, motivation and perception through surfacing metaphors participants associate with sexualized performance imagery. By exploring the attitudes of participants and how they perceive and asses sexualized performance imagery which combines athletic and appearance factors, this research contributes to literature about objectification and gathers empirical data in regards to the societal and cultural impact of these images which further gives insight about the dual identity theory and its literature. Using participant-gathered stimuli and imagery, this study will give an understanding of whether sexualized elements or athletic elements dominate for viewers in sexualized performance imagery and give advertising and marketing practitioners deep insights into how consumers perceive sexualized content and the emotional aspects that influences them and their attitudes.